Research on the Ground Vacuum Shortwave Calibration of Moon-Based Earth Radiation Budget Detector - Jieling Yu; Wei Fang; Duo Wu; Silong Wang; Zhitao Luo; Yuwei Wang; Yisu Zhang; Xin Ye (IEEE Photonics Journal)
The Moon-based Earth Radiation budget Detector (MERD) is an instrument designed to measure the Earth-reflected Solar Radiation (ERSR) and the Earth thermal radiation from the Moon as part of future mission of China's Chang'e project. The accuracy of its calibration technology directly determines the measurement precision. For traceability to International System of Units (SI) and improve the calibration accuracy in the ERSR wave band, a vacuum shortwave radiance calibration system is built, which consists of an in-situ traceable Electrical Substitution Transfer Radiometer (ESTR) and a Shortwave Calibration Light Source (SWCLS). Where, SWCLS is designed with a electrically variable slit and a 12-hole narrow-band filter wheel to achieve continuous broad-spectrum radiance output and discrete narrow-spectrum band tuning, respectively. Additionally, wide dynamic range output is from the introduction of elliptic land spherical mirrors for bilateral highly efficient focusing structure. This paper presents the mathematical process of shortwave calibration and focuses on the design and analysis of SWCLS based on high stability, radiance and uniformity. Results show that light source stability is 0.05922%/h, radiance uniformity is 99.49% at the calibration distance of 300 mm, the range of output radiant brightness in the spectral range 0.3–2.5 μm is 0.03–1272.20 W/m2/sr.